Threat assessment caused by mass removal in Jericó (Boyacá), during the winter of 2011 - Abril-González, Nebardo Arturo; Amaya-Reyes, Edwin Gilberto; Fonseca-Peralta, Héctor Antonio (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
During the heavy rainy season in the first half of 2011 they were presented in the town of Jericó, Boyacá, Colombia, landslides phenomena with disastrous consequences. Heavy rains caused various phenomena of removal in five villages, of which La Estancia was affected by a landslide that covered about 360 hectares and produced the evacuation of many families. Now, several families have returned and it is required to establish the degree of threat present there. Some geological and geotechnical studies have been made to assess the current level of stability and to define the necessary actions to enable the zone to agricultural activities.